Paraneoplastic neuromyelitis optica spectrum disorder: A case report and review of the literature - Annus, Ádám; Bencsik, Krisztina; Obál, Izabella; Kincses, Zsigmond Tamás; Tiszlavicz, László; Höftberger, Romana; Vécsei, László (Journal of clinical neuroscience, 2018)
Neuromyelitis optica spectrum disorders (NMOSD) are demyelinating, autoimmune diseases affecting the central nervous system. Typically, recurrent optic neuritis and longitudinal extensive transverse myelitis dominates the clinical picture. In most cases NMOSD are associated with autoantibodies targeting the water channel aquaporin-4 (AQP-4). NMOSD usually present in young adults. Clinical findings suggestive of NMOSD in elderly patients should raise the suspicion of a paraneoplastic etiology. To our knowledge, we report the first case of a 66 year-old female patient with paraneoplastic NMOSD that is associated with squamous cell lung carcinoma. Anti-AQP-4 was present in both the serum and cerebrospinal fluid of the patient. However, immunhistological staining of the malignant tissue did not show presence of AQP-4 on the surface of tumour cells.
Keywords: kouření; Aquaporin-4; Aged; magnetická rezonanční tomografie; nádory plic; paraneoplastická polyneuropatie; imunohistochemie; senioři; Neuromyelitis optica; Magnetic Resonance Imaging; lidé; neuromyelitis optica; Spine; Paraneoplastic; páteř; autoprotilátky; Smoking; Immunohistochemistry; Female; Lung Neoplasms; Autoantibodies; ženské pohlaví; Neuromyelitis Optica; Paraneoplastic Polyneuropathy; Humans; akvaporin 4; Aquaporin 4; spinocelulární karcinom; Carcinoma, Squamous Cell